PENGARUH LAMA DUDUK TERHADAP KASUS LOW BACK PAIN MYOGENIK DENGAN MODALITAS INFRARED DAN WILLIAM FLEXION EXERCISE PADA SISWA MADRASAH ALIYAH DI PEKANBARU - Ismaningsih Ismaningsih; Renni Hidayati Zein; Dian Cita Sari (LPPM Universitas Abdurrab, 2019)
Bacground. Low Back Pain Myogenic is a condition in which there is excessive muscle contraction in the lower back due to contraction or repetitive muscle use so that muscle tension.Purpose: The objective of this study is to investigate the differences between the effects of William Flexion Exercise and Infrared on sitdown activity student’s of MAN 2 Pekanbaru. Research Method: The study used experimental pre-test and post-test with two group designs. The research samples were 20 students taken through simple random sampling. The samples were divided into two groups. Group A was given William Flexion Exercise while group B was given Infrared.Result: There is no difference between the effect of William Flexion Exercise and Infrared on sitdown activity student’s. Suggestion: The other researchers are expected to conduct similar researches with longer research period.